Eating patterns and weight-related concerns among female adolescents in rural schools in Kota Bharu, Kelantan - Har, Lim Yoke (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Some of the typical eating patterns among adolescents include meal skipping, snacking, eating away from home, fast food consumption and unconventional dietary patterns like adopting vegetarian diet, specific weight loss diet, and an overall reduction of food intake. Eating has become one of the most important health topics due to the increasing prevalence and incidence rates of eating disorders among different groups of populations. Therefore, this cross-sectional study was conducted among female adolescents to investigate the eating frequency of three main meals, identify those who are at-risk of eating disorders, explore association of eating patterns, weight-related concerns, disordered eating, and Body Mass Index (BMI). Random cluster sampling method was applied and 2 schools had been selected from a total of 23 schools in rural area. Respondents were given self-administered questionnaire consisting socio-economic background, eating patterns, weight concerns, and EAT-26. From a total of 334 respondents, 45.2% was in Form 1 and the remaining was in Form 4. A higher proportion of form 4 respondents (72.1 %) skipped breakfast as compared to form 1 respondents (67.5%) [X2 (1) = 0.828, p = 0.363]. There was 18.6% ofthe total respondents atrisk of eating disorders. This study found more Form 4 respondents (19.1 %) at-risk of eating disorders compared to Form 1 respondents (17.9%) [X2 (1) = 0.085, p = 0.771]. However, no association found between disordered eating and breakfast skipping [X2 (1) = 0.561 , p = 0.454]. There is significant association between breakfast skipping and weight concern in this study [X2 (1) = 4.404, p = 0.036] but there is no significant association between disordered eating and weight concern in this study [X2 (1) = 2.997, p = 0.083]. A positive correlation was found between BMI and EAT-26 score (r5 = 0.240, p = 0.001). In conclusion, the prevalence of female adolescents at-risk of having eating disorders in rural area of Kota Bharu is comparable to other local studies in urban areas. Thus, nutritional education and public awareness are needed to improve eating behavior of female adolescents in this country.